2020
DOI: 10.19109/ejpp.v6i2.5518
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Visual Social Semiotics in English Textbook

Abstract: The objectives of the study were (1) to analyze the embedded meanings of visual images, and (2) to analyze the suitability between visual and written messages in an English textbook entitled “Pathway to English for SMA/MA Grade X”. The approach of this study was a qualitative one by using grounded theory method. The visual images and written text were analyzed by using the descriptive framework proposed by Kress and Leeuwen (2006). This study revealed that (1) the visual images embedded three visual meanings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…They prefer to use entertain lexemes, especially passive voices. These findings have a different model with those found by Qin and Karabacak (2010) and Qoriah (2020) who found that novice writers tend to use proclaim lexemes such as endorsement and announcing.…”
Section: Vignettecontrasting
confidence: 79%
See 1 more Smart Citation
“…They prefer to use entertain lexemes, especially passive voices. These findings have a different model with those found by Qin and Karabacak (2010) and Qoriah (2020) who found that novice writers tend to use proclaim lexemes such as endorsement and announcing.…”
Section: Vignettecontrasting
confidence: 79%
“…The researcher has conducted this research by using content analysis. To build the trustworthiness of this research, the researcher triangulated the data by three techniques: expert judgment, peer debriefing, and rich, thick description (Qoriah, 2020). Expert judgment was needed to check the quality of research.…”
Section: Engagement Contractmentioning
confidence: 99%
“…A load of aesthetic sense is more than other sense which highlights the purely decorative role of images and pictures (see Hill, 2003;Romney, 2012;Romney & Bell, 2012) rather than the educational role in these series. Whether decorative or educational, the visual content plays a significant role in the ELT textbook (Tomlinson, 2011) as a means of influencing students' interests and attitudes (Qoriah, 2020), recalling the information (Yaman, 2010), and enhancing students' communicative competence (Donaghy & Xerri, 2017) which is the main objective of this series based on the book's claim. However, the low quality might be a barrier to student engagement and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…To be more clearly, Karaman (2012) explained that the children book has many powerful characteristics in visual image such as in the children picture book and visual illustration on book is an important part of making a literary work. As mentioned by Tomlinson in Qoriah (2020) in through the role of visual image is to attract the reader and also can easily meaning-making for interpretation. Book and reader communication process are the things of the important role through book elements (Gudinavičius & Šuminas, 2018).…”
Section: Introductionmentioning
confidence: 99%